Tunnel depth effect to pile in Tunnel's influence zone. (February 2023) - Lim, Chun Xiang; Jusoh, Siti Norafida; Lim, Chin Boon; Abdullah, Rini Asnida; Mohd Yunus, Nor Zurairahetty
Abstract: The increased population in urban areas resulted in high demand for public facilities; hence, tunnels became popular, especially in developed countries. However, tunnel activity may alter the original ground equilibrium, leading to a ground stress release. These may result in an adverse pile response and potential hazard to a nearby building structure. Previous research focuses on the tunnel-pile interaction but solely investigates in homogeneous soil formation. Therefore, this paper presents the tunnel-pile-ground interaction with various tunnel depths in multiple soil formations. A three-dimensional model was developed by using the finite element method of ABAQUS based on Circle Line Stage 3 (C852) projects in Singapore. The models were carried out in two stages: first, by investigating the tunnel-induced ground movements (free-field condition) and second, with the presence of a pile. The tunnel model depth varied at respective ratios of C/D of 1, 2, 3, and 4. The results show, with a low tunnel depth ratio, a high maximum ground settlement is obtained. The longitudinal settlement trough presents a smooth surface settlement curve for free-field conditions, but a chimney-like transition at the pile periphery for conditions with the pile. The ground settlement trough for tunnelling near to adjacent pile leads to a skewed maximum settlement towards the pile. A higher C/D ratio produced higher lateral stress induced on the pile but the opposite for a lower C/D ratio. Pile was significantly affected and shown by extensive lateral stress for the pile body that lies parallel to the tunnel depth. Highlights: Pile integrity due to nearby tunnel might affected. Due to the tunnel's influence zone, a settlement in a flatted chimney pattern can be seen at the pile head surrounding. The settlement is significant for a shallow tunnel in the soft ground formation.